Finance and Development, March 1973. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1973)
This paper analyzes the issue of migrant workers in Europe. The paper highlights that the number of migrant workers currently in the major industrialized countries of Western Europe is not accurately known. The actual annual flow of migration into Western Europe has been growing rapidly in recent years. Most migrants are so-called annual or permanent workers, although in France, particularly in agriculture, and in Switzerland, 'seasonal' migration is also important. The paper also highlights that the sectoral distribution of migrant workers tends to follow the pattern of sectoral employment growth in the receiving country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet